Surfactant-free synthesis, photocatalytic and electrochemical property study of Co3O4 nanoparticles. (April 2018) - Huang, Zhifang; Zhao, Yan; Xu, Haitao; Zhao, Jingzhe
Graphical abstract: Highlights: Surfactant-free Co3 O4 nanoparticles were synthesized in aqueous solution. The size of Co3 O4 nanoparticles can be controlled by changing the NaOH concentration. The Co3 O4 nanoparticles size bears a linear relationship to the NaOH concentration. The photocatalytic and electrochemical properties of Co3 O4 nanoparticles are size dependent. Abstract: A facile surfactant-free route for size-control preparation of Co3 O4 nanoparticles in aqueous solution was reported. The feeding ratio of OH − to Co 2+ influences the conversion of Co 2+ to Co3 O4 crystals, and affects the crystallinity of the final Co3 O4 products. The size of Co3 O4 nanoparticles can be controlled to be 15, 18, 27 and 30 nm by simply regulating the concentration of NaOH solution through a β- Co(OH)2 → Co3 O4 process. A linear relationship between Co3 O4 size and NaOH concentration was found. The photocatalytic property for rhodamine B (RhB) degradation and electrochemical property for supercapacitor of the Co3 O4 nanoparticles are size dependent. Co3 O4 nanoparticles in the size of 15 nm showed the highest photocatalytic efficiency of 70% in pH 3 under visible-light irradiation for 3 h, and behaved the highest specific capacitance of 177 F g −1 .